Dampak Multikulturalisme terhadap Pendidikan Islam Studi Literatur Kepustakaan - Hamdan Hamdan (Al-Munawwarah : Jurnal Pendidikan Islam, 2023)
This paper aims to discuss the impact of multiculturalism on Islamic education through a literature review. Multiculturalism is a global phenomenon that affects people's lives in various aspects including education. In the context of Islamic education, multiculturalism influences the paradigms, methods, and curriculum of Islamic education. This paper uses qualitative methods using a phenomenological approach. Phenomenology is the science that studies phenomena or symptoms. Data tracing is carried out through various literary sources such as books, journals, and scientific articles related to the theme discussed. The findings of this study reveal that multiculturalism has a significant impact on Islamic education, where the paradigm shift of Islamic education becomes more inclusive and adaptive. The requirements for multiculturalism education can work if there is tolerance, respect for differences, and cooperation. In developing a multicultural curriculum, teaching materials are needed that accommodate student diversity, and the establishment of a learning environment that is inclusive and respects differences. Thus, Islamic education can develop a more inclusive paradigm and accommodate diversity in society. The challenges of implementing multiculturalism in Islamic education are differences in religious interpretations, stereotypes and prejudices, controversies over the use of language, and local cultural influences.